2016
DOI: 10.1016/j.tsf.2016.01.045
|View full text |Cite
|
Sign up to set email alerts
|

In situ X-ray diffraction studies on the piezoelectric response of PZT thin films

Abstract: International audiencePiezoelectric properties of randomly oriented self-polarized PbZr0.50Ti0.50O3 (PZT) thin films were investigated using in situ synchrotron X-ray diffraction. Possibilities for investigating the piezoelectric effect using microsized hard X-ray beams are demonstrated and perspectives for future dynamical measurements on PZT samples with variety of compositions and thicknesses are given. Studies performed on the crystalline [100, 110] directions evidenced piezoelectric anisotropy. The piezoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…in situ X-ray diffraction experiments were performed at the DiffAbs beamline at SOLEIL synchrotron (St Aubin, France) [23,24]. The incident monochromatic 10 keV X-ray beam was collimated to a size of 50 µm using a pinhole placed about 20 cm upstream of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…in situ X-ray diffraction experiments were performed at the DiffAbs beamline at SOLEIL synchrotron (St Aubin, France) [23,24]. The incident monochromatic 10 keV X-ray beam was collimated to a size of 50 µm using a pinhole placed about 20 cm upstream of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous report demonstrated that the piezoelectric properties of polycrystalline PZT thin films was larger than that of epitaxial PZT thin films 16 . In this study, to understand the crystallographic factors contributing to the macroscopic piezoelectric properties, we performed in-situ X-ray diffraction (XRD) measurements 1824 on PZT thin films using a synchrotron radiation source. Here, we demonstrate one of the first comparative discussions that evaluates the macroscopic piezoelectric properties and the microscopic deformation of crystal structures of epitaxial and polycrystalline Pb(Zr,Ti)O 3 (PZT) thin films.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular materials are ZnO, BaTiO 3 , AlN, and lead zirconate titanate. [3][4][5][6][7][8] Even though the aforementioned materials exhibit high piezoelectric performance, they lack flexibility and environment-friendliness. In this regard, poly(vinylidene fluoride) (PVDF)-based systems have gained tremendous popularity due to their flexibility, mechanical stability, thermal stability, and chemical inertness.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of materials with relatively high piezoelectric performance has been studied enormously. The most popular materials are ZnO, BaTiO 3 , AlN, and lead zirconate titanate . Even though the aforementioned materials exhibit high piezoelectric performance, they lack flexibility and environment‐friendliness.…”
Section: Introductionmentioning
confidence: 99%